Strategi Lobi dan Negosiasi pada Event P-Land: K-Pop Art Market dalam Melakukan Kerja Sama dengan Sponsor - Eka Arfita, Willa; Dwi Ratna Dewi, Liza (Journal of Comprehensive Science, 2025)
In the era of globalization and digitalization, communication strategy has an important role in establishing relationships between organizations and stakeholders. In the K-Pop-themed event industry, success is not only determined by the attractiveness of the event, but also the ability of the organizers to establish strategic cooperation with sponsors. This study aims to analyze the lobbying and negotiation strategies applied to the P-LAND: K-Pop Art Market event, using Robert Cialdini's six principles of persuasion: reciprocation, commitment dan consistency, social proof, liking, authority, and scarcity. This study uses a qualitative descriptive method with in-depth interviews, observations, and documentation as data collection techniques. The results of the study show the application of persuasion principles that support the success of lobbying and negotiation strategies. The principle of reciprocity is applied through exclusivity to sponsors such as promotional booths and content collaboration. Commitment and consistency are realized by maintaining consistent communication and fulfilling agreements. Social proof is reinforced by showcasing the success of previous events. The authority principle relies on the role of the project manager in negotiations, while the preference principle builds positive personal relationships. The principle of scarcity is utilized by emphasizing the exclusivity of cooperation. This research fills in the gap in the study of the application of the principle of persuasion in K-Pop-themed events in Indonesia. Theoretically, this study enriches communication strategies in Public Relations, while in practice, it provides guidance to improve the effectiveness of lobbying and negotiations with sponsors in the event industry.